RETRACTED: Synthesis of Bioactive Yttrium-Metal–Organic Framework as Efficient Nanocatalyst in Synthesis of Novel Pyrazolopyranopyrimidine Derivatives and Evaluation of Anticancer Activity - Saleh, Raed Obaid; Achmad, Harun; Daminov, Botir Turgunpulatovich; Kzar, Hamzah H.; Mahdi, Ahmed B.; Hammid, Ali Thaeer; Abid, Mohammed Kadhem; Opulencia, Maria Jade Catalan; Mustafa, Yasser Fakri; Sharma, Himanshu (Frontiers in Chemistry, 2022)
Novel Yttrium-metal organic framework (Y-MOF) was synthesized in optimal conditions of microwave in power of 20 W, temperature of 30 degree of centigrade and time duration 10 min. the products were characterized by SEM (morphology and size distribution), TGA (thermal stability), BET technique (surface area) and FTIR (characterization of related group). The Yttrium-metal organic framework (Y-MOF) synthesized in this study, after identifying and confirming the structure, was used as an efficient and recyclable catalyst in the synthesis of new pyrazolopyranopyrimidines derivatives. Following the study of the properties and applications of Y-MOF, its anticancer properties on breast cancer cells based on the MTT method were evaluated and significant results were observed. In addition, the anticancer properties of the pyrazolopyranopyrimidines derivatives were investigated.